2017
DOI: 10.1038/s41598-017-08419-7
|View full text |Cite
|
Sign up to set email alerts
|

Forces and Disease: Electrostatic force differences caused by mutations in kinesin motor domains can distinguish between disease-causing and non-disease-causing mutations

Abstract: The ability to predict if a given mutation is disease-causing or not has enormous potential to impact human health. Typically, these predictions are made by assessing the effects of mutation on macromolecular stability and amino acid conservation. Here we report a novel feature: the electrostatic component of the force acting between a kinesin motor domain and tubulin. We demonstrate that changes in the electrostatic component of the binding force are able to discriminate between disease-causing and non-diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 78 publications
2
22
0
Order By: Relevance
“…The affinity of the S and ACE2 and the stability of RBD-ACE2 complex are hence important to be investigated. We have applied the structure-based tools to quantitatively assess the effects of damaging mutations on protein stability and proteinprotein interaction (18)(19)(20). In the present study, we applied saturation mutagenesis to investigate 18,354 missense mutations in SARS-CoV-2 S, 3,705 mutations in SARS-CoV-2 RBD, and 11,324 mutations in hACE2.…”
Section: Introductionmentioning
confidence: 99%
“…The affinity of the S and ACE2 and the stability of RBD-ACE2 complex are hence important to be investigated. We have applied the structure-based tools to quantitatively assess the effects of damaging mutations on protein stability and proteinprotein interaction (18)(19)(20). In the present study, we applied saturation mutagenesis to investigate 18,354 missense mutations in SARS-CoV-2 S, 3,705 mutations in SARS-CoV-2 RBD, and 11,324 mutations in hACE2.…”
Section: Introductionmentioning
confidence: 99%
“…The main differences between these two predicted states are the hot spots residues identified for each situation, even though some of these hot spots repeat within the interface for both approaches (Tables 1 and 2). Several studies have shown how electrostatic forces contribute to PPIs, including those related to diseases development [67][68][69]. Figure 1C and 1D show a predicted mode of interaction between eNOS and p53 regarding hydrophobic-favored and Van der Waals-favored coefficients, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Electrostatic forces are frequently omitted from the analysis of e®ect of mutations, however, recently it was demonstrated that the changes of electrostatic forces due to mutations can be used to discriminate pathogenic from benign mutations. 73 There are no many resources available for modeling electrostatic forces in molecular biology with the prominent exception of DelPhiForce. 74,75 This tool allows for modeling the electrostatic forces acting on individual atom(s), residue(s) or molecular partners.…”
Section: Electrostatic Forcesmentioning
confidence: 99%